2010
DOI: 10.1071/hc10061
|View full text |Cite
|
Sign up to set email alerts
|

A special type of 'hard-to-reach' patient: experiences of pregnant women on methadone

Abstract: INTRODUCTION: Opiate addicts in New Zealand are a heterogeneous, hard-to-reach group with illicit drug activity as their common characteristic. This project investigated the experience of a specific hardto-reach group: pregnant women with opiate dependency, focussing on their interactions with helping services and social networks. The aim was to explore the interactions of pregnant women on methadone with helping services and social support, with the objective to make recommendations to improve service to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Other studies that assess quantitatively the determinants of methadone dose changes during pregnancy could not be identified. A recent qualitative study of health service staff and opioid‐dependent women on MMT reported that women expressed concerns about dose safety and neonatal withdrawal . The authors also noted that women resist recommended dose increases out of concerns for the neonate, and that family members may put women under pressure to lower their methadone dose during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that assess quantitatively the determinants of methadone dose changes during pregnancy could not be identified. A recent qualitative study of health service staff and opioid‐dependent women on MMT reported that women expressed concerns about dose safety and neonatal withdrawal . The authors also noted that women resist recommended dose increases out of concerns for the neonate, and that family members may put women under pressure to lower their methadone dose during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis reported that there was no consistent statistically significant difference in the incidence of NAS with differing doses of methadone . In spite of this, women frequently request detoxification or dose reductions during pregnancy, in the hope of avoiding NAS .…”
Section: Introductionmentioning
confidence: 99%
“…Patients' trust that a health care provider cares about them and works in their best interest is considered foundational to the provider-patient relationship and is associated with positive health outcomes (Birkhauer et al, 2017). When pregnant and postpartum women and health care providers do not form trusting relationships, inadequate prenatal care and missed opportunities to improve health outcomes for women and their infants can result (Chan & Moriarty, 2010;Gilchrist et al, 2012;Leppo, 2012).…”
Section: Substance Use and Health Care Experiences In Pregnancy And Pmentioning
confidence: 99%
“…Pregnant and postpartum women with SUDs report fear of criminalization or punishment if their substance use is reported to authorities by health care providers (Chan & Moriarty, 2010;Gilchrist et al, 2012;Hall & van Teijlingen, 2006;Harvey et al, 2015;Howard, 2015;Jessup et al, 2003;Leppo, 2012;Stone, 2015). Fear of loss of infant custody, arrest, prosecution, or incarceration can thus impair the formation of trust in the provider-patient relationship, serve as a barrier to the utilization of prenatal care and addiction treatment services, and discourage disclosure of substance use to health care providers (Kruk & Banga, 2011;Phillips et al, 2007;Roberts & Nuru-Jeter, 2010;Roberts & Pies, 2011;Stengel, 2014;Stone, 2015;Van Scoyoc et al, 2016).…”
Section: Substance Use and Health Care Experiences In Pregnancy And Pmentioning
confidence: 99%
“…The researchers conclude that a fresh look at services to the hard-to-reach may be beneficial. 9 While ear sunctioning or syringing is commonly performed in general practice to remove ear wax causing symptoms such as discomfort, tinnitus or hearing loss, a case review from the United Kingdom warns us that even the most common and benign of medical interventions can have serious or fatal adverse effects. 10 This issue's Charms and Harms deals with the herbal remedy black cohosh, which has inconclusive evidence of efficacy but real safety issues with regard to potential liver toxicity.…”
mentioning
confidence: 99%